Establishing the baselines of Diplolaimella dievengatensis (Nematoda: Monhysteridae) for life-history experiments - Oliveira, N. R.; Cunha, B. P.; Vilas-Boas, A. C.; Gallucci, F.; Monteiro, L.; Custódio, M. R.; Fonseca, G. (Zoologischer Anzeiger, 2021)
Biological data about nematode populations are generally very scarce. Once species are isolated and cultivated in laboratories, they are used in experimental assays without deeper prior knowledge of their life-history characteristics. Hence, in this study, we aimed to determine the life history and population characteristics, as well as to evaluate the morphometric and molecular aspects (18S rDNA) of a free-living estuarine nematode species Diplolaimella dievengatensis. This species was isolated from an estuary in Southeastern Brazil and cultivated in the laboratory under conditions similar to its local environment. The obtained data was compared with specimens from Belgium and Pakistan that were available in the literature. For the Pakistani strain, only morphometric parameters were available. The intrinsic rate of natural increase (individuals per day-1) was slightly higher for the Brazilian population (rm = 0.41 ind/day) than for the Belgium population (rm = 0.348 ind/day), probably due the higher generation time (14 days) of the Belgium population when compared to the Brazilian individuals (10.3 days). Brazilian population showed a linear and continuous pattern of somatic growth, different from the exponential growth reported for the Belgium population. The analysis of morphometric data of D. dievengatensis individuals from the three distinct locations (Brazil, Belgium and Pakistan) showed large variability. The multivariate analysis showed that the Brazilian specimens were isometrically larger than Pakistani and Belgian ones. Nevertheless the morphometric variables used for the diagnosis, such as a and c rates, overlapped among them. Molecular comparison of the 18S sequence showed more than 99% similarity of the Brazilian specimens with the Belgium sequences from the Genbank. Acknowledging such intraspecific variability across the different dimensions may help to understand distinct responses of the population in nature.